Fraud Dalam Pengelolaan Keuangan Desa Adat (Studi Kasus Pada Desa Adat Jimbaran Kabupaten Badung) - I Made Anjol Wiguna; Atmadja, Anantawikrama Tungga; Yuniarta, Gede Adi (Jurnal Ilmiah Akuntansi dan Humanika, 2022)
This study aims to find out the background of why fraud occurs, know the process of fraud, and the implications of fraud in the financial management of indigenous villages. This research is qualitative research using primary data sourced from interviews, observations, and document studies. The results of this study show that fraud in the financial management of jimbaran traditional villages occurs because it is backgrounded by the lack of critical attitude towards traditional village prajuru, as well as the intentions of traditional village prajuru using positions. The existence of fraud is caused by weak village padruwen rules and governance, the influence of ewuh pakewuh culture, rationalization attitudes, and cultural capital factors. The process of fraud in the financial management of the Jimbaran Traditional Village is caused by opportunities and opportunities. The short-term implication that can be caused by fraud from the perpetrator's side is the mental pressure felt by the fraud perpetrators because they have to perform a bendu piduka ceremony in front of the krama. The long-term implication arising from fraud is the level of trust in indigenous villages in later periods. This research can be used as a reference for customary villages when supervising the performance of customary village prajuru, and can be used as a reference by customary village prajuru to prevent fraud in the financial management of customary villages